The Effectiveness of Geopark-Based Science Learning to Increase Students’ Concern for The Local Environment and Culture the Belitung Island - Budiastra, A. A. Ketut; Asror, Mustaghfiri; Erlina, Nia; Wicaksono, Iwan (Advances in Social Sciences Research Journal, 2023)
Research to know the effectiveness of science learning at the Geopark-based elementary school (SD) stage on Belitung Island which includes geological diversity (Geodiversity), biodiversity (Biodiversity), and cultural diversity (Cultural diversity). The type of research applied is experimental research with a one-group pretest-posttest design. The sample selected was elementary school students in grades IV, V, and VI with each class using a large scale. The instruments used were pretest and posttest to determine student learning outcomes in geopark-based science learning both before and after the learning process. In this study, questionnaires were also used to collect qualitative descriptive data. The research results for grade IV geological diversity on granite teaching materials show that Geopark-based science learning is effectively applied in the high category and for Lake Kaolin teaching materials show that Geopark-based science learning is effectively applied in the medium category. The results of the research for Biodiversity for class V Mangrove Forest teaching materials show that Geopark-based science learning is effectively implemented in the high category and for Kabong Tree or Enau teaching materials it is shown that Geopark-based science learning is effectively applied in the medium category. The results of the study for cultural diversity (Cultural diversity) for class VI on Marastaun Culture teaching materials show that Geopark-based science learning is effectively applied with medium category and for Nirok Nanggok Culture teaching materials shows Geopark-based science learning is effectively applied with high category. The research recommendations show that development in the form of Geopark-based science teaching materials needs to be followed up for learning in the Geopark area which is a source of the nation’s natural wealth.